1997
DOI: 10.3109/00016349709050063
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arginine vasopressin on breathing movements of chronically instrumented fetal lambs

Abstract: AVP has an inhibitory effect on FBM. The mechanism of this inhibition was not a direct suppression of the CNS as there was a dissociation between FBM and the electrocortical activity during infusion of AVP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The values of hematocrit for sheep of all ages, market‐age sheep, lambs, and fetal sheep are reported in Tables 17 , 18 , 19 , and 20 , respectively. The hematocrit for sheep of all different ages was calculated based on 24 studies (Alhidary et al., 2012 ; Anosa & Isoun, 1976 ; Bessho et al., 1997 ; Campbell et al., 2014 ; Carver & Hay, 1995 ; Ceï et al., 2018 ; Degen & Young, 1981 ; Gomes et al., 2013 ; Hart & Doyle, 1985 ; Horton & Burgher, 1992 ; Jobe et al., 1998 ; Maraba et al., 2018 ; Marsh et al., 2001 ; Matson et al., 1981 ; Mayland et al., 1986 ; Meyer‐Gesch et al., 2013 ; Rege et al., 2002 ; Robillard & Weitzman, 1980 ; Roghair et al., 2004 ; Saylor & Leach, 1980 ; Singh et al., 2018 ; Talke et al., 1985 ; Tran et al., 2000 ; Vannucchi et al., 2012 ), and the average value was 36.15% (Table 17 ). The value of hematocrit for goats was calculated based on five different studies (Anosa & Isoun, 1976 ; Courtice, 1943 ; McKean & Walker, 1974 ; Olsén et al., 2013 ; Olsson et al., 1994 ), and the average value was 29.38% (Table 21 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The values of hematocrit for sheep of all ages, market‐age sheep, lambs, and fetal sheep are reported in Tables 17 , 18 , 19 , and 20 , respectively. The hematocrit for sheep of all different ages was calculated based on 24 studies (Alhidary et al., 2012 ; Anosa & Isoun, 1976 ; Bessho et al., 1997 ; Campbell et al., 2014 ; Carver & Hay, 1995 ; Ceï et al., 2018 ; Degen & Young, 1981 ; Gomes et al., 2013 ; Hart & Doyle, 1985 ; Horton & Burgher, 1992 ; Jobe et al., 1998 ; Maraba et al., 2018 ; Marsh et al., 2001 ; Matson et al., 1981 ; Mayland et al., 1986 ; Meyer‐Gesch et al., 2013 ; Rege et al., 2002 ; Robillard & Weitzman, 1980 ; Roghair et al., 2004 ; Saylor & Leach, 1980 ; Singh et al., 2018 ; Talke et al., 1985 ; Tran et al., 2000 ; Vannucchi et al., 2012 ), and the average value was 36.15% (Table 17 ). The value of hematocrit for goats was calculated based on five different studies (Anosa & Isoun, 1976 ; Courtice, 1943 ; McKean & Walker, 1974 ; Olsén et al., 2013 ; Olsson et al., 1994 ), and the average value was 29.38% (Table 21 ).…”
Section: Resultsmentioning
confidence: 99%
“… Note The hematocrit of sheep with all ages was calculated based on 24 studies (Alhidary et al., 2012 ; Anosa & Isoun, 1976 ; Bessho et al., 1997 ; Campbell et al., 2014 ; Carver & Hay, 1995 ; Ceï et al., 2018 ; Degen & Young, 1981 ; Gomes et al., 2013 ; Hart & Doyle, 1985 ; Horton & Burgher, 1992 ; Jobe et al., 1998 ; Maraba et al., 2018 ; Marsh et al., 2001 ; Matson et al., 1981 ; Mayland et al., 1986 ; Meyer‐Gesch et al., 2013 ; Rege et al., 2002 ; Robillard & Weitzman, 1980 ; Roghair et al., 2004 ; Saylor & Leach, 1980 ; Singh et al., 2018 ; Talke et al., 1985 ; Tran et al., 2000 ; Vannucchi et al., 2012 ). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…General surgical procedures are described in detail elsewhere (9). Briefly, four pregnant cross-bred ewes were anesthetized by intramuscular Rom-puni@ with additional use of Lidocaine.…”
Section: Methodsmentioning
confidence: 99%
“…Intravenous infusions of AVP transiently decrease pulmonary ventilation and phrenic nerve activity in conscious dogs ( Ohtake and Jennings, 1993 ), anesthetized and awake rats ( Louwerse and Marshall, 1993 ; Walker and Jennings, 1998 ; Żera et al, 2018 ; Brackley and Toney, 2021 ) and fetal lambs ( Bessho et al, 1997 ). Recently published pilot study in patients with autosomal dominant polycystic kidney disease showed that upon initiation of treatment with tolvaptan, a selective V2R antagonist, plasma copeptin level increased 6-fold and this was associated with a modest but significant increase in arterial carbon-dioxide and plasma acidity ( Heida et al, 2021 ), suggestive of ventilatory inhibition by increased AVP levels in the bloodstream and enhanced stimulation of V1 receptors, which were not blocked by tolvaptan.…”
Section: The Respiratory Effects Of Vasopressinmentioning
confidence: 99%